2005
DOI: 10.1111/j.1475-1313.2004.00241.x
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal electroretinography in isolated arterially perfused bovine eye

Abstract: Isolated arterially perfused bovine eye may be used as an experimental model to study retinal electrophysiology using mfERG. The in vitro eye may offer a convenient and easily obtainable alternative to live animals, particularly for drug screening and invasive studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Maintenance of outer retina function was determined by the presence of a stable ERG response as determined by each individual study. Of the eight studies, seven used flash ERG,27 3033 35 36 and one used multifocal ERG (mfERG) 34. Two of the eight studies reported that without reperfusion, ERG activity is greatly decreased or absent within 5 min after enucleation 27 32.…”
Section: Resultsmentioning
confidence: 99%
“…Maintenance of outer retina function was determined by the presence of a stable ERG response as determined by each individual study. Of the eight studies, seven used flash ERG,27 3033 35 36 and one used multifocal ERG (mfERG) 34. Two of the eight studies reported that without reperfusion, ERG activity is greatly decreased or absent within 5 min after enucleation 27 32.…”
Section: Resultsmentioning
confidence: 99%
“…Most have used positive pressure to force artificial perfusates [including Eagle's basal medium (Gouras and Hoff, 1970); Hank's salts (Niemeyer, 1975), modified Kreb's solution (Shahidullah et al, 2005), tissue culture medium (Peachey et al, 1993), and oxygenated blood (Tazawa and Seaman, 1972;Tseng et al, 1989)] into the eye. We have used modified Kreb's solution or oxygenated blood for ex vivo perfusion and demonstrated that ERG activity is maintained with these perfusates.…”
Section: Discussionmentioning
confidence: 99%
“…Bovine eyes were perfused using a method described in earlier studies on aqueous humor formation and multifocal electroretinogram (Shahidullah et al, 2003(Shahidullah et al, , 2005. The ophthalmic artery was cannulated and the eye perfused with a physiologic saline.…”
Section: Methodsmentioning
confidence: 99%